Penerapan Metode Demonstrasi Mencampur Warna Untuk Meningkatkan Kemampuan Kognitif Pada Anak Didik Kelompok B1 Semester I Di TK Widya Kumara Duda Selat Karangasem - Ni Nyoman Sri Astiti (Jayapangus Press, 2021)
The ability and activity of children in mixing colors at the initial condition is still very low. Classroom action research was conducted to improve cognitive ability to recognize colors, namely aspects of pointing colors, calling colors and mixing colors. The subjects of the study were 20 people in the group B1 TK Widya Kumara Selat Duda. This study aims to describe the implementation of the demonstration method and the results of learning to recognize colors, designed in two cycles consisting of planning, implementation, observation/assessment and reflection stages. Data were collected by observing the ability of children's learning outcomes and analyzed by qualitative descriptive analysis. The indicator of the average success of learning outcomes is in category B (Good). Based on the learning outcomes from pre-cycle 15% improvement in learning outcomes in cycle I showed that there was an increase in cognitive ability to recognize colors from 20% to 50% and in cycle II there was an increase in cognitive ability to recognize. Thus, it was concluded that the application of the demonstration method was able to improve the cognitive ability to recognize the color of the students of group B1 TK Widya Kumara Selat Duda Karangasem.